PELATIHAN PERHITUNGAN HARGA POKOK PRODUKSI USAHA LAUNDRY DI BEKASI JAWA BARAT - Nilawati, Yuana Jatu; Budi, Ali Gesang Widodo; Mayangsari, Mayangsari (Jurnal Berdaya Mandiri, 2020)
Micro, small and Medium Enterprise (MSMEs) is ) is a prosperous driving industry to help people get jobs and income for their lives. Along with the development of MSMEs from each year, the mortality rate for MSMEs also increases. One of the problems faced by MSME entrepreneurs is an error in incorrect pricing. Problems like this will create fatal mistakes that will result in failure in determining the selling price and in the long run produce financial statements that are not in accordance with the reality of the field. COGS from service products provided to its customers, by calculating the exact COGS the laudry entrepreneurs can obtain income in accordance with what they want and avoid mistakes in determining the selling price. From this reason, it is necessary to conduct training for MSME entrepreneurs to calculate COGS so that the business started can develop and sustainble